The Concept of «Yurt» in the literature of Central Asia - Kogay, Je. R. (Eurasian Journal of Philology Science and Education, 2018)
The article deals with the substantial components of the basic concept of «Yurt ». National-cultural and individual layers are identified. It holds in-detail description of the «passive layer» of the concept of «Yurt». As the material of description the works of the famous contemporary writers Aitmatov Ch. and Kanapyanov B. and Kerbabaev B. were considered. The researcher highlights language means that represent the concept of «Yurt»: lexical units in the literal sense, metaphorical designations, comparisons, epithets, figurative associations, symbolic assimilation. The focusing on the context of language units representing the concept of «Yurt» gives an opportunity to reveal the periphery of the concept, to describe the meaning shades that are not fixed in any lexicographical sources.